Determination of K4000 of potential blazar candidates among EGRET unidentiﬁed gamma-ray sources - Uwitonze, Emmanuel; Nkundabakura, Pheneas; Mutabazi, Tom (Proceedings of the International Astronomical Union, 2019)
Blazars are radio-loud Active Galactic Nuclei (AGN) with relativistic jets oriented towards the observer’s line-of-sight. Based on their optical spectra, blazars may be classiﬁed as ﬂat-spectrum radio quasars (FSRQs) or BL Lacs. FSRQs are more luminous blazars with both narrow and broad emission and absorption lines, while BL Lacs are less luminous and featureless. Recent studies show that blazars dominate (∼93%) the already-identiﬁed EGRET sources (142), suggesting that among the unidentiﬁed sources (129) there could still be faint blazars. Due to the presence of a strong non-thermal component inside their jets, blazars are found to display a weaker depression at ∼4000˚A (K4000≤0.4). In this study, we aimed at determining the K4000 break for a selected sample among the potential blazar candidates from unidentiﬁed EGRET sources to conﬁrm their blazar nature. We used two blazar candidates, 3EG J1800-0146 and 3EG J1709-0817 associated with radio counterparts, J1802-0207 and J1713-0817, respectively. Their optical counterparts were obtained through spectroscopic observations using Robert Stobie spectrograph (RSS) at the Southern African Large Telescope (SALT) in South Africa. The observed Ca II H&K lines depression at ∼4000˚A in spectra of these sources show a shallow depression, K4000 = 0.35±0.02 and 0.24±0.01, respectively, suggesting that these sources are blazar candidates. Moreover, the redshifts z = 0.165 and 0.26 measured in their spectra conﬁrm the extragalactic nature of these sources.
Keywords: Line; Identiﬁcation; Radiation mechanisms; Non-thermal; Techniques; Spectroscopic; Galaxies; Active; Galaxies; Jets; Galaxies; BL Lacertae objects